(untitled) (Research, Society and Development, 2020)
With the objective to evaluate the effects of nitrogen levels (0, 40, 80, 120 and 160 kg of N ha-1) on green dry matter (GDM) yield and morphogenetic and structural characteristics and nitrogen nutrition index (NNI) of Brachiaria brizantha cv. Piatã, was installed an experiment under field conditions in Roraima´s savannas. Nitrogen fertilization increased significantly (P<0.05) GDM yields, number of tillers, number of leaves tiller-1, average leaf size, leaf area index, leaf senescence rate, leaf appearance and elongation rates. Maximum GDM yields, leaf elongation rates, leaf length and number of leaves tiller-1 were obtain with the application of 145.9; 118.2; 108.9 and 133.6 kg of N ha-1, respectively. Nitrogen nutrition index alone with 120 or 160 kg N application was higher than the grass N internal critical level. The NNI, efficiency of utilization and apparent N recovery were inversely proportional to the increased N levels.